2019
DOI: 10.3390/polym11091474
|View full text |Cite|
|
Sign up to set email alerts
|

Phase Diagrams of n-Type Low Bandgap Naphthalenediimide-Bithiophene Copolymer Solutions and Blends

Abstract: Phase diagrams of n-type low bandgap poly{(N,N′-bis(2-octyldodecyl)naphthalene -1,4,5,8-bis(dicarboximide)-2,6-diyl)-alt-5,5′,-(2,2′-bithiophene)} (P(NDI2OD-T2)) solutions and blends were constructed. To this end, we employed the Flory–Huggins (FH) lattice theory for qualitatively understanding the phase behavior of P(NDI2OD-T2) solutions as a function of solvent, chlorobenzene, chloroform, and p-xylene. Herein, the polymer–solvent interaction parameter (χ) was obtained from a water contact angle measurement, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Figure 1 shows the chemical structures of (a) P(NDI2OD-T2) and (b) PCPDTBT. In the previous works, we reported that the solubility parameter (δ) of P(NDI2OD-T2) is 7.99 [22], whereas that of PCPDTBT (M n = 3.2 kg/mol and PDI = 2.2) is 10.70 [21]. Note that in this work, PCPDTBT has M n = 4.5 kg/mol and PDI = 3.0, indicating a very minor difference between the two PCPDTBT samples.…”
Section: Film Characterizationmentioning
confidence: 44%
See 4 more Smart Citations
“…Figure 1 shows the chemical structures of (a) P(NDI2OD-T2) and (b) PCPDTBT. In the previous works, we reported that the solubility parameter (δ) of P(NDI2OD-T2) is 7.99 [22], whereas that of PCPDTBT (M n = 3.2 kg/mol and PDI = 2.2) is 10.70 [21]. Note that in this work, PCPDTBT has M n = 4.5 kg/mol and PDI = 3.0, indicating a very minor difference between the two PCPDTBT samples.…”
Section: Film Characterizationmentioning
confidence: 44%
“…Note that in this work, PCPDTBT has M n = 4.5 kg/mol and PDI = 3.0, indicating a very minor difference between the two PCPDTBT samples. Hence, based on the former δ data, the Flory–Huggins interaction parameter ( ) [ 22 , 39 , 40 ] for the PCPDTBT/P(NDI2OD-T2) polymer blends could be estimated using Equation (1), where (= lattice site volume) and were the molar volume of a solvent [ = (112.56 g/mol)/(1.11 g/cm 3 ) = 101.41 cm 3 /mol for CB] and the solubility parameter [subscript i or j = 1, 2; PCPDTBT = 1 and P(NDI2OD-T2) = 2]. R and T were the gas constant and temperature (K).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations